2018
DOI: 10.13189/ujer.2018.060803
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Functional Movement Screen and Athletic Performance in Children Tennis Players

Abstract: FMS is one of the test battery that is used very common recently. Asymmetries and limitations of the functional movement patterns could be detected with this test battery. Study's purpose was to evaluate the relationship between FMS and athletic performance parameters in prepubertal children. 28 male children voluntarily participated in the study (Age: 9.6 ± 0.7 years, Height: 134.1 ± 6.8 cm, Weight: 31.3 ± 4.1 kg, and Training Duration: 3.1 ± 1.3 years). In study's results, a very significant relationship was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…On the other hand, it was noted that the jump performance of the athletes with high FMS ® scores (> 14) were better, their knee muscle strengths were higher, and their H:Q ratios were more balanced. In accordance with results of our study, Yıldız (2018) identified that FMS ® scores presented higher correlation values with CMJ performance in 28 male tennis players (r = 0.570, p = .002). This result was a result we expected, because the potential performance outputs of the vertical jump capability can be estimated in the FMS ® test battery with the Deep Squat, which requires a vertical force production.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it was noted that the jump performance of the athletes with high FMS ® scores (> 14) were better, their knee muscle strengths were higher, and their H:Q ratios were more balanced. In accordance with results of our study, Yıldız (2018) identified that FMS ® scores presented higher correlation values with CMJ performance in 28 male tennis players (r = 0.570, p = .002). This result was a result we expected, because the potential performance outputs of the vertical jump capability can be estimated in the FMS ® test battery with the Deep Squat, which requires a vertical force production.…”
Section: Discussionsupporting
confidence: 92%
“…QMP represents flexibility and stability, which are the first level of functional movement, and according to the “Performance Pyramid Model” of Cook and colleagues [ 28 ], this first level supports other levels, like endurance, strength, speed, and power. Yıldız et al reported that QMP has a significant association with agility and acceleration in child tennis players [ 60 ] and with flexibility and vertical jumping in elite Karate athletes [ 61 ]. While there is no evidence reporting the relationship between QMP and FMS, Lester et al [ 62 ] combined QMP and FMS assessment in primary children but did not discuss any association.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a plethora of research on the use of the FMS in adults, there is growing scientific evidence indicating the use of the FMS in youth. Studies to date have been performed in the United States, Canada [ 42 , 43 ], Hungary and Germany [ 44 , 45 ], Italy [ 46 ], Moldova [ 38 ], countries of the UK [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Ireland [ 58 , 59 ], Poland [ 60 , 61 , 62 , 63 , 64 ], Slovakia [ 65 ], Iran [ 66 , 67 , 68 ], Turkey [ 69 , 70 , 71 , 72 , 73 , 74 ], Japan [ 75 ], China [ 76 , 77 ], Thailand [ 32 ], Taiwan [ 78 , 79 , 80 ], Korea [ 81 ], Indonesia [ 82 ], Croatia [ 40 , 41 , 83 , 84 ], Brazil [ 85 ], Portugal [ 86 ], Spain [ 87 , 88 , 89 , 90 …”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
“…,54,55,[57][58][59]62,63,[76][77][78][81][82][83][84][86][87][88][89][91][92][93]103,108], some include only boys[43,46,47,50,51,53,56,61,64,66,[68][69][70][71][72][73][74][75]80,85,90,94,97,[100][101][102]105,106,109] and some studies do not report the sex of the participants at all[14,52,…”
mentioning
confidence: 99%